Master of Science in Rangeland Ecosystem Management Curriculum - Mwamburi, Mcharo; Kambura, Ann; Gacheru, James; Maghenda, Marianne; Jalang'o, Dorcas; Waswa, Boaz Shaban; Kinyua, Ivy Wambui; Templer, Noel; Mwongera, Caroline (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The combination of inadequate understanding of the dynamics in rangeland ecosystems and local livelihood systems are to blame for the inappropriate policy actions, unabated rangeland degradation trends, impoverishment of communities living in the rangelands, and their increased vulnerability to various shocks including climate change. The root cause of these problems is mainly linked to lack of inadequate skilled human resources, trained in rangeland ecosystem management at the postgraduate level, to tackle the complex biodiversity interactions in the rangeland ecosystems. The philosophy of this degree programme is, therefore, anchored in the paradigm that rangelands are socio-ecological systems with complex biophysical, socio-cultural and economic interactions, which call for specialized managers and decision makers. This programme therefore, aims to produce a critical mass of rangeland ecosystem management experts equipped with requisite skills, technologies and innovations to further research, apply appropriate practices and influence policies in favour of resilient rangeland ecosystems and livelihoods. Trained skilled manpower is expected to act as a catalyst for enhancing the productivity and sustainability of rangeland ecosystems and livelihoods through practice, policies and research.